Distribution of in-situ stress and regional structural influence in the Luxin mining area and engineering applications - Lang Lu; Feng Wang; Jun Mu; Jianqiang Mi; Baohong Chen; Pingping Zhao (Scientific Reports)
Abstract In-situ stress is a significant factor in the occurrence of dynamic disasters in coal mines. Measured data from 22 measuring points in the Luxin mining area was analyzed to investigate the distribution of in-situ stress and regional structure action. The results reveal that in-situ stress in the Luxin mining area is predominantly a structure stress, it is mainly manifested in the medium and low stress levels. The maximum horizontal principal stress, minimum horizontal principal stress, and vertical principal stress are 5.47–18.8 MPa, 3-10.15 MPa, and 4.8–12.5 MPa, respectively, all of them are positively correlated with the burial depth. As the burial depth increases, the discreteness of the maximum and minimum horizontal principal stresses first increases and then decreases. The lateral pressure ratio varies from 0.6 to 2.1, gradually approaching 1 with increasing depth, and the discreteness gradually decreases with the increase of depth and its discreteness gradually decreases. The differences between maximum and minimum horizontal principal stress range from 2.47 to 9.6 MPa. The predominant direction of the maximum horizontal principal stress in the Luxin mining area is NW. The influence of the F1 and F2 reverse faults alters this direction, with seven measuring points indicating a maximum horizontal principal stress direction of N (21.4°-78.6°) E. From the axis of the Xishan anticline to the bottom of the flanks, the maximum horizontal principal stress generally increases. The F1 and F2 reverse faults cause stress redistribution, leading to fluctuations in the maximum horizontal principal stress in the hanging wall region of these faults. The distribution of in-situ stress in Luxin Mining Area is the result of the combined action of the Xishan anticline, faults and torsional stress in the north-south direction. The distribution of in-situ stress in Luxin Mining Area is the consequence of the combined effect of the Xishan anticline, faults, and torsional stress in the north-south direction. Based on the measured in-situ stress data from Shadunzi coal mine, a roadway support scheme for the S4103 working face was developed, which improved roadway stability.